Utilization of corn gluten meal as a protein source in the diet of white shrimp Litopenaeus vannamei. (17th November 2014) - Molina‐Poveda, C.; Lucas, M.; Jover, M.
Abstract: A 57‐day feeding trial was designed to assess the potential of corn gluten meal (CGM) as a plant protein source in practical feeds for white shrimp Litopenaeus vannamei . Five experimental diets providing 350 g kg −1 protein and 110 g kg −1 lipid were prepared, where 0%, 25%, 50%, 75% and 100% of fishmeal (FM) protein was substituted by protein from CGM. The results showed that partial or complete replacement of FM with CGM did not affect survival. The growth of the shrimp declined as the levels of CGM increased, diets containing CGM showing a significantly lower final weight (3.2–5.9 g) and specific growth rates (1.7–2.7% per day) compared to those fed on the diet with 0 CGM (7.1 g and 3.0% per day). Feed conversion ratio was also significantly affected by CGM level. The inclusion of CGM resulted in a statistical decrease in the apparent digestibility (AD) of dry matter from 77.9% to 66.0% and in AD of protein from 80.5% to 52.0%, of feed. The AD of amino acids, with the exception of lysine, declined with the dietary incorporation of CGM. In summary, reduced palatability, low protein digestibility and a deficiency of lysine and methionine seem to be the major reasons behind a depressed growth in shrimp fed on CGM protein‐based diets.